[Co(2, 2′-bipy)3]Ag3I6 with a hole structure facilitates dye adsorption and photocatalytic reduction. Issue 44 (8th November 2022) - Tang, Chunying; Sun, Yawei; Liu, Jianbiao; Xu, Qinfeng; Zhang, Chun-yang
Abstract : We demonstrate that [Co(2, 2′-bipy)3 ]Ag3 I6 with a hole structure facilitates dye adsorption and photocatalytic reduction. Abstract : We synthesized a new iodoargentate [Co(2, 2′-bipy)3 ]Ag3 I6 (1 ) (2, 2′-bipy = 2, 2′-bipyridine) via the reaction of AgI, KI, 2, 2′-bipy and Co(NO3 )2 in dimethylformamide (DMF) solvent at room temperature. The [Co(2, 2′-bipy)3 ] 3+ complex cation directs the formation of the 0 D cluster [Ag3 I6 ] 3− anion that features an irregular double-level gear wheel with a maximum diameter of 5.512 Å. The iodoargentate possesses the characteristics of semiconductors with a band gap of 2.03 eV. It exhibits excellent ion-exchange behavior for adsorbing crystal violet (CV) and methylene blue (MB), and it can function as a promising photocatalyst for degrading rhodamine B (RhB). The improved photocatalytic activity can be ascribed to the hole structure in the anions of iodoargentates.